Pathogenicity of Aseptic Bursaphelenchus xylophilus - Zhu, Li-hua; Ye, Jianren; Negi, Sapna; Xu, Xu-ling; Wang, Zhang-li; Ji, Jin-yi (PloS one, 2012)
Pine wilt is a disease of pine (Pinus spp.) caused by the pine wood nematode (PWN), Bursaphelenchus xylophilus. However, the pathogenic mechanism of pine wilt disease (PWD) remains unclear. Although the PWN was thought to be the only pathogenic agent associated with this disease, a potential role for bacterial symbionts in the disease process was recently proposed. Studies have indicated that aseptic PWNs do not cause PWD in aseptic pine trees, while PWNs associated with bacteria cause wilting symptoms. To investigate the pathogenicity of the PWN and its associated bacteria, 3-month-old microcuttings derived from certain clones of Pinus densiflora Siebold & Zucc. produced in vitro were inoculated under aseptic conditions with aseptic PWNs, non-aseptic PWNs and bacteria isolated from the nematodes. Six-month-old aseptic P. densiflora microcuttings and 7-month-old P. massoniana seedlings were also inoculated under aseptic conditions with aseptic PWNs and non-aseptic PWNs. The results showed that the aseptic microcuttings and seedlings inoculated with aseptic PWNs or non-aseptic PWNs wilted, while those inoculated with bacterial isolates did not wilt. Nematodes were recovered from wilted microcuttings and seedlings inoculated with aseptic PWNs and non-aseptic PWNs, and the asepsis of nematodes recovered from aseptic PWN-inoculated microcuttings and seedlings was reconfirmed by culturing them in NB liquid medium at 30°C for more than 7 days. Taken together, the results indicate that the asepsis of PWN did not cause the loss of pathogenicity.